1998
DOI: 10.1038/2079
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based training for the treatment of partial blindness

Abstract: Partial blindness after brain injury has been considered non-treatable. To evaluate whether patients with visual-field defects can profit from computer-based visual restitution training (VRT), two independent clinical trials were conducted using patients with optic nerve (n = 19) or post-chiasmatic brain injury (n = 19). In post-chiasma patients, VRT led to a significant improvement (29.4%) over baseline in the ability to detect visual stimuli; in optic nerve patients, the effects were even more pronounced (73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
206
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(231 citation statements)
references
References 15 publications
15
206
2
6
Order By: Relevance
“…Judging the patients vision loss based solely on detection accuracy in perimetry underestimates the subjective visual impairment. This has also implication for neurovisual rehabilitation methods such as vision restoration training [25,27], non-invasive current stimulation [66,67], or both combined [68,69]. They might be used to also improve these less obvious deficits in the intact visual field sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judging the patients vision loss based solely on detection accuracy in perimetry underestimates the subjective visual impairment. This has also implication for neurovisual rehabilitation methods such as vision restoration training [25,27], non-invasive current stimulation [66,67], or both combined [68,69]. They might be used to also improve these less obvious deficits in the intact visual field sector.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HRP provides an excellent spatial resolution and enables reaction time recording and analysis. Details of HRP are described elsewhere [16,[24][25][26][27].…”
Section: Clinical Examinationmentioning
confidence: 99%
“…The primary outcome measure used for this review was functional ability in activities of daily living, with secondary outcome measures including extended activities of daily living, visual field, balance, falls, depression/anxiety, discharge destination, quality of life, visual scanning, adverse events, and death. The review was limited to randomized trials and studies included in Cochrane systematic reviews involving adult stroke patients, and a total of thirteen studies met the authors’ inclusion criteria (Roth et al., 2009; Bainbridge & Reding, 1994; Carter, Howard, & O'Neil, 1983; Jobke, Kasten, & Sabel, 2009; Kasten, Wüst, Behrens‐Baumann, & Sabel, 1998; Kasten, Bunzenthal, Müller‐Oehring, Mueller, & Sabel, 2007; Plow et al., 2010; Poggel, Kasten, & Sabel, 2004; Rossi, Kheyfets, & Reding, 1990; Spitzyna et al., 2007; Szlyk, Seiple, Stelmack, & McMahon, 2005; Weinberg et al., 1977, 1979). The Cochrane authors concluded there is some limited evidence to support the use of compensatory scanning therapy to improve scanning and reading outcomes in this patient group.…”
Section: Resultsmentioning
confidence: 99%
“…Although this view still holds true, it has been challenged and reassessed by many authors, who have demonstrated that the visual system continues to mature and respond to environmental changes even in adulthood (Fregnac, Shulz, Thorpe, & Bienenstock, 1988;Karni & Sagi, 1991;Sale, et al, 2011). This notion of visual network plasticity is paramount not only in helping us achieve a better understanding of the human visual system and of visual plasticity mechanisms, but also in identifying noninvasive treatment tools and protocols to provide visual rehabilitation following injury, such as hemianopia following stroke (Huxlin, et al, 2009;Kasten, Wust, Behrens-Baumann, & Sabel, 1998), amblyopia, and even when the visual deficit is at the non-cortical level such as in cases of myopia and presbyopia. In the latter case especially, being able to manipulate neuroplasticity might help us achieve visual recovery through compensatory strategies (Camilleri, Pavan, Ghin, Battaglini, & Campana, 2014;Casco, et al, 2014;Durrie & McMinn, 2007;Tan & Fong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…So far, PL has been shown to be effective in improving, among other dysfunctions, visual abilities in amblyopia (Campana, Camilleri, Pavan, Veronese, & Lo Giudice, 2014;Hussain, Webb, Astle, & McGraw, 2012;Levi & Li, 2009;Li, Young, Hoenig, & Levi, 2005;Polat, 2009;Polat, Ma-Naim, Belkin, & Sagi, 2004;Zhou, et al, 2006), mild refractive defects like myopia (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Tan & Fong, 2008) and presbyopia (Polat, et al, 2012), and central or peripheral vision loss and cortical blindness (Chung, 2011;Das, Tadin, & Huxlin, 2014;Huxlin, et al, 2009;Kasten, et al, 1998;Plank, et al, 2014;Rosengarth, et al, 2013;Sabel, Kenkel, & Kasten, 2005). In myopia, visual input is limited by an optical de-focus, despite normal neuronal connectivity and image processing.…”
Section: Introductionmentioning
confidence: 99%